Sampah Dapur Dan Sampah Daun Dengan Campuran Kotoran Sapi Untuk Pembuatan Biogas - Trisnaningsih, Anis; Widyastuti, Sri (WAHANA, 2015)
The degradation of organic matter under anaerobic conditions, to produce a gas which is largely composed of a mixture of methane and carbon dioxide. This study aims to assess variations in the composition of kitchen waste, leaf litter with cow dung, measures the time the fermentation process and measure the rate of increase in gas pressure. Benefits of the research are expected to use waste kitchen waste, leaf litter and cow dung as an alternative energy source that is inexpensive and environmentally friendly. Experiments in this study conducted using household biogas reactor made of drum. The medium used for the growth of microorganisms is EM4. Leachate water samples obtained from the fermentation of garbage. Parameters measured were carbon, nitrogen, salmonella and mercury using measurement 1 methods for testing carbon-Organic conducted using Walkey and Black, test Nitrogen using semi-micro Kjeldahl modified, test Mercury by using qualitative analysis and quantitative mercury with tools Mercury Analyzer, Isolation and identification of Salmonella sp follow the Food and Drug Administration (FDA, 1995). Colonies that appear red with black middle gram staining, colony subsequently was identified towards Salmonella sp. biochemically. Biogas reactor performance is determined by measuring the increase in pressure and compare the variety of media used. The results obtained by the gas pressure is highest in the first variation is between 33-38 cm of water column takes about 11-12 days to produce the most gas. As for the second variation of the gas pressure generated by 29 cm column of water with gas formation time of 12 days and 3 variations of the gas pressure generated at 22-23 cm of water column with gas formation time of 11-12 days. Flame test done to prove the gas produced is methane (CH₄) instead of CO₂. From the results of the laboratory, leachate can not use a liquid organic fertilizer because it found Salmonella.